Exchange bias in ferromagnetic nanoparticles embedded in an antiferromagnetic matrix. (2nd May 2005) - Nogues, J.; Sort, J.; Langlais, V.; Doppiu, S.; Dieny, B.; Munoz, J.S.; Surinach, S.; Baro, M.D.; Stoyanov, S.; Zhang, Y.
The fabrication process and magnetic properties of three types of system consisting of ferromagnetic (FM) particles embedded in an antiferromagnetic (AFM) matrix are discussed. The preparation techniques are ball milling, H2 partial reduction of oxides and nanoparticle gas condensation. The magnetic properties of the FM/AFM composites are shown to depend strongly on the morphology of the system (e.g., nanoparticle size), the AFM anisotropy and the AFM-FM coupling. For example, all the studied systems exhibit coercivity enhancement below the Neel temperature of the AFM. However, while Co nanoparticles embedded in CoO exhibit loop shifts of thousands of Oe, Fe nanoparticles in Cr2 O3 only show a few Oe shifts. An interesting effect evidenced in all systems is the increase of remanence (MR ) which, in the case of Co-CoO, ultimately leads to an improvement of the superparamagnetic blocking temperature of the nanoparticles.